Bilateral Minithoracotomy for Mitral Valve Repair and Coronary Bypass Grafting - Fagu, Albi; Pingpoh, Clarence; Berger, Tim; Siepe, Matthias (The Thoracic and Cardiovascular Surgeon Reports, 2023)
Background Combined mitral valve and coronary artery surgery is usually accomplished via a median sternotomy and is associated with increased mortality and morbidity.Case Description We report on a 67-year-old patient with mitral valve regurgitation and concomitant coronary artery disease (CAD). The mitral valve was repaired using the loops and ring technique, and the left anterior descending artery was revascularized using the left internal mammary artery through a bilateral minithoracotomy approach. The postoperative course was uneventful.Conclusion Patients with mitral valve pathologies and concomitant CAD can be successfully operated via a bilateral minithoracotomy approach.
Keywords: minimally invasive surgery; mitral valve; surgery; coronary artery bypass grafting; CABG